Consumer preferences for solid biomass fuels for energy purposes - Zlateva, Penka; Yordanov, Krastin; Murzova, Mariana; Terziev, Angel (International Journal of Renewable Energy Development, 2025)
A specialized marketing survey was conducted across wholesale markets, manufacturing enterprises, online platforms and retail stores in Bulgarian market to analyze consumer preferences for various types of pellets. The study aims to identify key factors influencing consumer choices, with a particular focus on pellet qualities like ash content and the impact of additives on the combustion process. Statistical analysis of the survey results reveals that manufacturing enterprises are the most preferred purchase channels due to the superior quality of their products, while pellets from online platforms often receive negative feedback due to quality issues. Based on the findings, four types of pellets with and without additives are selected for further analysis: 100% coniferous; a mix of 80% coniferous and 20% deciduous; a mix of 80% coniferous and 20% sunflower and 100% sunflower pellets. To confirm the combustion characteristics of these pellet types, thermogravimetry (TG) and differential scanning calorimetry (DSC) analyses are conducted at heating rates of 5°C/min and 10°C/min up to 600°C. The analysis of variance (ANOVA) on the TG data shows significant differences in mass loss during thermal treatment between the various pellet types, demonstrating differences in efficiency and quality. The results indicate that sunflower pellets produce more ash, while wood pellets have superior combustion properties with lower ash generation. These findings highlight the need for improved consumer awareness, especially regarding the impact of pellet composition and additives on ash production. The correlation analysis of the DSC data reveals that some pellet types exhibite a high degree of similarity, suggesting they could be used interchangeably in combustion systems, while other types show significant differences due to varying raw material compositions. The study concludes that improving combustion processes requires careful selection of pellet fuels tailored to specific system needs and emphasizes the importance of better labeling and clearer information on pellet composition to enhance consumer knowledge and promote best practices in biomass fuel usage.